Review of Law Number 41 of 2004 Regarding the Practice of Swapping (Ruislag) of Mosque Waqf Land Outside the Context of Public Interest in Wringinputih Village, Banyuwangi Regency - Khasanah, Dewi Siti; Hisan , Moh. Syifaul (Syarah: Jurnal Hukum Islam dan Ekonomi, 2024)
The practice of waqf in Indonesia has undergone modernization, including the management of waqf assets, which is often carried out through exchanges or swaps to maximize their benefits. Although the legality of such exchanges is clearly regulated under Law Number 41 of 2004, cases in the field still reveal violations of these regulations. This condition is driven by a lack of awareness regarding the importance of preserving waqf assets for community welfare and insufficient understanding of the applicable legal provisions. This research aims to investigate the practice of land exchange (ruislag) involving mosque waqf land conducted without considering public interest, focusing on the legal framework outlined in Law Number 41 of 2004 concerning Waqf. The study employs a qualitative approach, using the village of Wringinputih, Muncar subdistrict, Banyuwangi regency, as a case study. The research methods include observation, in-depth interviews with relevant parties, and analysis of related legal documents. The findings reveal that the practice of exchanging mosque waqf land in Wringinputih Village, Banyuwangi Regency, unrelated to public interest, occurred due to an offer from a particular party to exchange land. However, the land's status had not been officially transferred to the mosque. A prior agreement had been made between the heirs and the party involved in the land exchange. Following the handover, the mosque accepted and received the waqf. An examination of Law Number 41 of 2004 indicates that the land exchange practice involving the waqf land of Bustanul Arifin Mosque in Wringinputih Village, Banyuwangi, did not fully comply with the regulations. The discrepancies include the exchange being motivated by personal interest, the uncertified status of the land, and the lower value of the replacement land compared to the original.